Estudio de los procesos de manipulación e higiene en la producción de conservas de frutas en el laboratorio de la Unidad Académica CAREN-UTC. 2016. Diseño de un manual de buenas prácticas de manufactura. - Chicaiza Guanoluisa, Wilson Javier, Ing. (2016)
This research project was conducted at the Fruits Laboratory of the UTC, it is located in the neighborhood Salache Bajo, in the parish Eloy Alfaro. Its purpose was the study of the processes of handling and hygiene in the preparation of fruit preserves, through inspections in the laboratory of the academic unit CAREN - UTC. It was necessary to determine the knowledge possessed by students who made academic practices at the Fruits Laboratory, then the percentage of compliance with GMP that exist in the laboratory was established and then information on hygiene and handling processes that allowed the development of GMP manual was compiled. The study was justified by having theoretical value, practical value and social relevance. It is supported on theories of hygiene and handling fruit for canning and food quality systems. The population was forty students from 8th and 9th cycle Agroindustrial Engineering and all areas of the Fruits Laboratory. The instruments used were: a questionnaire with eighteen basic questions that should know food handlers and a check list with articles related to GMP of sanitary standard for processed foods, food processing plants, distribution establishments, marketing, transportation and collective food establishments, which it was applied while the laboratory is inspected. The results were: students with good knowledge in food handling and Fruits Laboratory compliance with the sixty-three percent of good manufacturing practices. It concluded that the application of BPM in the Fruits Laboratory should be improved, especially in the quality control of the products by having 93% of default. It is also necessary to use standard operating procedures and records evidencing the activities.